2019
DOI: 10.3758/s13414-019-01869-3
|View full text |Cite
|
Sign up to set email alerts
|

Is it impossible to acquire absolute pitch in adulthood?

Abstract: Absolute pitch (AP) refers to the rare ability to name the pitch of a tone without external reference. It is widely believed to be only for the selected few with rare genetic makeup and early musical training during the critical period, and therefore acquiring AP in adulthood is impossible. Previous studies have not offered a strong test of the effect of training because of issues like small sample size and insufficient training. In three experiments, adults learned to name pitches in a computerized, gamified … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 116 publications
(223 reference statements)
2
16
1
Order By: Relevance
“…We aimed at recruiting as many exchange students as possible in a 3-month period, and ended up training 13 exchange students at the Chinese University of Hong Kong (six males, mean age = 21.23, SD = 3.98). The sample size required was estimated using GPower 3.1.9.2 based on our previous training study on tonal language speakers (Wong et al, 2020). In that study, a large effect size was observed for the improvement in adults during the generalisation test (pretest vs. posttest; average normalη p 2 = .701 across three experiments for trained tones).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…We aimed at recruiting as many exchange students as possible in a 3-month period, and ended up training 13 exchange students at the Chinese University of Hong Kong (six males, mean age = 21.23, SD = 3.98). The sample size required was estimated using GPower 3.1.9.2 based on our previous training study on tonal language speakers (Wong et al, 2020). In that study, a large effect size was observed for the improvement in adults during the generalisation test (pretest vs. posttest; average normalη p 2 = .701 across three experiments for trained tones).…”
Section: Methodsmentioning
confidence: 99%
“…The training was adapted from a previous study (Wong et al, 2020). It was gamified and structured into 30 levels, organised into 10 three-level parts with increasing number of pitches (from 3 to 12; Figure 2a).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations